Meningkatkan komponen kebugaranjasmani atlet bola tangan melalui latihan Tabata pada saat terjadinya wabah COVID-19 - Setiawan, E.; Tri Iwandana, D.; Festiawan, R.; Baptista, C. (Jurnal SPORTIF Jurnal Penelitian Pembelajaran, 2020)
The purpose of this research was to improve the handball athletes` physical fitness through Tabata training during the outbreak of COVID-19. This pre-experimental research used a One-Group Pretest-Posttest Design. The research participants were male handball athletes at amateur level (N = 30) (age = 21.8 ± 1.3 years, height = 169.6 ± 2 cm, weight = 60.7 ± 7 kg). All participants performed the Tabata training for 23 sessions with a frequency of 3 times a week. The athletes` physical fitness level was measured using push-ups, curl-ups, V-sit and reach, as well as shoulder stretch. All research data were then analyzed using SPSS version 22 with a significance level of a 0.05. The results of this research found that the physical fitness components consisting of strength endurance (P<0.05), muscle strength (P>0.251), flexibility in the area of lower back and hamstrings (P<0.05) as well as upper arm flexibility (P<0.05) experienced differences before and after performing the Tabata training program. It is concluded that in response to the outbreak of COVID-19 throughout the world, Tabata is one alternative training to be performed by each handball athlete at home since Tabata training may provide various benefits in improving the handball atlethes` physical fitness components